2019
DOI: 10.1002/ppul.24522
|View full text |Cite
|
Sign up to set email alerts
|

Improving outcomes of infections in cystic fibrosis in the era of CFTR modulator therapy

Abstract: Currently, available single and dual‐combination cystic fibrosis transmembrane conductance regulator (CFTR) modulator therapies have favorably altered the life course of individuals with cystic fibrosis (CF) by decreasing morbidities and increasing survival. However, even with CFTR modulator use, questions and challenges remain to optimize the management of lung infections. This review (a) identifies these ongoing challenges and discusses the current understanding of the potential impact of CFTR modulator ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 46 publications
0
27
0
1
Order By: Relevance
“…However, it is claimed that at least 90 percent of Canadian CF patients could eventually benefit from such CFTR modulators as they improve and become the standard of care [ 8 ]. In addition to its expanding scope, the implementation of personalized medicines into healthcare systems has introduced complexities for policy and regulation.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is claimed that at least 90 percent of Canadian CF patients could eventually benefit from such CFTR modulators as they improve and become the standard of care [ 8 ]. In addition to its expanding scope, the implementation of personalized medicines into healthcare systems has introduced complexities for policy and regulation.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the decreased sputum loads of P. aeruginosa after ivacaftor therapy rebounded later in most samples ( Hisert et al., 2017 ). This phenomenon suggests other measures for controlling infection should be applied in parallel to reach the best treatment effect ( Saiman, 2019 ). Besides, although fungi and viruses exist in CF respiratory specimens, the effect of modulator therapy on them is unknown.…”
Section: How Cftr Modulator Therapies Affect the Airway Microbiomementioning
confidence: 99%
“…An ongoing clinical trial may untangle potential antagonism between inhaled tobramycin and chronic oral azithromycin in CF: Testing the Effect of Adding Chronic Azithromycin to Inhaled Tobramycin (TEACH; NCT02677701), randomizes participants to receive inhaled tobramycin with azithromycin vs. placebo [29].…”
Section: Azithromycinmentioning
confidence: 99%